2009
DOI: 10.1242/jcs.032615
|View full text |Cite
|
Sign up to set email alerts
|

Apical trafficking in epithelial cells: signals, clusters and motors

Abstract: In the early days of epithelial cell biology, researchers working with kidney and/or intestinal epithelial cell lines and with hepatocytes described the biosynthetic and recycling routes followed by apical and basolateral plasma membrane (PM) proteins. They identified the trans-Golgi network and recycling endosomes as the compartments that carried out apical-basolateral sorting. They described complex apical sorting signals that promoted association with lipid rafts, and simpler basolateral sorting signals res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
281
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(292 citation statements)
references
References 187 publications
7
281
0
Order By: Relevance
“…The proteins are then probably packaged in vesicular endosomes that are directed to the apical membrane (5,36). Studies on a variety of apical proteins have revealed several alternative routes of vesicular trafficking (41). In some cell types, ENaC appear to be transported in membrane lipid raft domains (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins are then probably packaged in vesicular endosomes that are directed to the apical membrane (5,36). Studies on a variety of apical proteins have revealed several alternative routes of vesicular trafficking (41). In some cell types, ENaC appear to be transported in membrane lipid raft domains (5).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins include SNARE type proteins such as syntaxin (3), Rab GTPases (29), and G proteins (17). The list of proteins involved is probably longer than we currently recognize (41).…”
Section: Discussionmentioning
confidence: 99%
“…4). This suggests that the reduction in pIgR-A580V transcytosis is likely due to reduced cleavage (13,16,17). …”
mentioning
confidence: 99%
“…This appears not to be a case, as a number of proteins (such as VSVG and the LDL receptor) have been reported to use a Rab8-positive sub-population of endosomes as an intermediate station on their way to the basolateral PM in epithelial cells (Ang et al, 2004), while others cargoes (such as E-cadherin, for example) move to the PM through a Rab11-containing endocytic compartment (Lock and Stow, 2005). Furthermore, ablation of the different endocytic compartments through horseradish peroxidase (HRP)-catalyzed crosslinking has revealed a number of apical proteins to take various through-endosome routes to reach the cell surface (Weisz and Rodriguez-Boulan, 2009). It remains to be understood, however, whether any cross-talk between these routes exists.…”
Section: Pgc Transition To the Target Membranementioning
confidence: 99%